2022
DOI: 10.3390/cells11172745
|View full text |Cite
|
Sign up to set email alerts
|

ACTN2 Mutant Causes Proteopathy in Human iPSC-Derived Cardiomyocytes

Abstract: Genetic variants in α-actinin-2 (ACTN2) are associated with several forms of (cardio)myopathy. We previously reported a heterozygous missense (c.740C>T) ACTN2 gene variant, associated with hypertrophic cardiomyopathy, and characterized by an electro-mechanical phenotype in human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). Here, we created with CRISPR/Cas9 genetic tools two heterozygous functional knock-out hiPSC lines with a second wild-type (ACTN2wt) and missense ACTN2 (ACTN2mut) alle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…Five µg protein was processed for LC-MS/MS analysis, as previously described. 47 Briefly, protein was reduced (2.5 mM dithiothreitol, Sigma-Aldrich; 30 min at 37°C) and alkylated (10 mM iodacetamide, Sigma-Aldrich; 15 min at 37°C) before proteolytic digestion with LysC (enzyme to protein ratio 1:100, Promega) for 3 h and with trypsin (1:25, Promega) for 16 h both at 37°C. The reaction was stopped with 1% acetic acid (Sigma-Aldrich), and the peptide mixtures were desalted on C-18 reverse phase material (ZipTip μ-C18, Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Five µg protein was processed for LC-MS/MS analysis, as previously described. 47 Briefly, protein was reduced (2.5 mM dithiothreitol, Sigma-Aldrich; 30 min at 37°C) and alkylated (10 mM iodacetamide, Sigma-Aldrich; 15 min at 37°C) before proteolytic digestion with LysC (enzyme to protein ratio 1:100, Promega) for 3 h and with trypsin (1:25, Promega) for 16 h both at 37°C. The reaction was stopped with 1% acetic acid (Sigma-Aldrich), and the peptide mixtures were desalted on C-18 reverse phase material (ZipTip μ-C18, Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Here we present a lower-cost bioreactor-based cardiac differentiation protocol (~$569 per bioreactor run yielding ~124 million hiPSC-CMs, compared to ~$1075 for ML differentiation with comparable yield, exclusive of manpower; Table S3) with defined benchmarks and controlled freeze/thaw procedures. We extensively characterized the resulting bCMs and demonstrated that they have robust structural and functional properties of cardiomyocytes, reduced batch-to-batch variation, and greater force production in EHTs than previously described 5,[16][17][18][32][33][34]36 . These levels of force were comparable to EHTs that underwent physical conditioning of increasing intensity 35 .…”
Section: Discussionmentioning
confidence: 91%
“…The results revealed several features of HCM including myofibrillar disarray, cardiomyocyte hypertrophy, impaired relaxation, hypercontractility, increased myofilament calcium sensitivity, and prolonged action potential duration (Prondzynski et al, 2019). A recent study by Zech et al involved used iPSC-CMs heterozygous and homozygous for this ACTN2 variant (p.Thr247Met) and showed multinucleation, cardiomyocyte hypertrophy, and myofibrillar disarray in the cellular models (Zech et al, 2022).…”
Section: Alpha-actinin Two and Cardiomyopathiesmentioning
confidence: 99%
“…Global inactivation of alpha-actinin two in mice is not compatible with life, but a cardiac specific mosaic inactivation suggests a crucial role of the protein for cardimyocyte maturation via serum response factor signaling (Guo et al, 2021). Moreover, a role of alpha-actinin two in regulating cardiac mitochondrial function has been proposed recently (Zech et al, 2022), in part by acting as a scaffold for mitochondrial messenger RNAs via binding to RNA-binding proteins (Ladha et al, 2020).…”
Section: Structure and Function Of Alpha-actininmentioning
confidence: 99%